ANALISIS PENGARUH RENTABILITAS TERHADAP RASIO KECUKUPAN MÓDAL PADA BANK TABUNGAN PENSIUNAN NASIONAL - Laurence A Manullang (Media Riset Bisnis & Manajemen, 2002)
The objective of this research is to examine the performance of BTPN Bank from 5 aspects point of views; Asset Quality, Liguidity, Profitability, Retum on Asset, Retum of Equity to improve its CAR eventually. Then the datas were analysedby using descriptive analysis method (Financial Ratio Analysis) and statistical analysis method (Correlation Analysis and Simple Regression) Minitab and Microsoft Excel programs. The result shows their rentability has insignificant correlation with capital.